THE ROLE OF VILLAGE GOVERNMENT IN MANAGING POWER PLANTS (PLTS) IN TANJUNG BATU KECIL VILLAGE, KARIMUN REGENCY - Farras; Afrizal, Afrizal; Putra, Ardi (Madika: Jurnal Politik dan Governance, 2025)
In a country's governance, electricity plays a vital role in supporting employee performance, optimizing public services, and enhancing community productivity. However, many villages in Indonesia still do not have access to 24-hour electricity; one such village is Tanjung Batu Kecil in Karimun Regency. In response to this issue, the Ministry of Energy and Mineral Resources provided assistance in the form of three Solar Power Plant (PLTS) units, each with a capacity of 30 kWp, located in Dusun I Tanjung Batu Kecil, Dusun II Pelakar, and Dusun III Kampung Baru. This study aims to analyze the role of the Village Government in managing the Solar Power Plants (PLTS) in Tanjung Batu Kecil Village, Karimun Regency. The research background is based on the existence of PLTS units as aid from the central government through the Ministry of Energy and Mineral Resources, which were handed over to the village government to be managed in order to meet the electricity needs of the community. In practice, the management of PLTS across the three hamlets shows varied outcomes: the PLTS in Dusun III remains operational, while those in Dusun I and II have become damaged and non-functional. This research employs a descriptive qualitative approach using Ryaas Rasyid's theory of government roles, which includes three indicators: as a dynamisator, facilitator, and regulator, with a total of 15 informants. The findings reveal that the Village Government plays a significant role in planning, organizing, and supervising the PLTS, although challenges remain in terms of coordination, maintenance, and community fee management, leading to operational disparities among the hamlets. Therefore, strengthening the village government's capacity and increasing active community involvement are key to achieving sustainable PLTS management.